Myocardial involvement in end-stage renal disease patients with anemia as assessed by cardiovascular magnetic resonance native T1 mapping: An observational study - Chen, Lin; Xu, Rong; Xu, Huayan; Yang, Zhigang; Zhang, Yi; Li, Zhenlin; Xia, Chunchao; Rao, Li; Guo, Yingkun (Medicine (Baltimore), 2024)
Cardiovascular disease has become to the main cause of death in the patients with end-stage renal disease (ESRD), and anemia is associated with increased cardiovascular morbidity and mortality in these patients. This study aimed to explore the impact of anemia on myocardial fibrosis using T1 mapping technique in patients with ESRD. A total of 128 subjects including 98 ESRD patients (65 with anemia, 33 without anemia) and 30 normal controls were enrolled. All subjects were underwent cardiovascular magnetic resonance to obtain cardiac cine and T1 mapping images. As potential markers of fibrosis, native T1 values and global longitudinal strain derived by feature-tracking technique were compared. Differences between 3 groups were analyzed using one-way analysis of variance. Associations between variables were assessed by Pearson and Spearman correlation coefficient appropriately. An independent association was identified by the multiple stepwise linear regression analysis. Intraclass correlation was applied to assess observer variability. In all ESRD patients, native T1 values were significantly longer than those of normal controls (global T1, 1357 ± 42 ms vs 1275 ± 48 ms, P < .001). Global T1 value in ESRD patients with anemia was significantly higher (1375 ± 36 ms) compared to that in ESRD patients without anemia (1322 ± 25 ms) and normal controls (1275 ± 48 ms), respectively (all P < .001). Global T1 correlated with hemoglobin negatively (R= −0.499, P < .001). Multiple stepwise linear regression analysis presented the anemia is independently associated with global T1 (R = 0.607, P < .001). Global longitudinal strain was remarkably reduced in ESRD patients with anemia in comparison to those without anemia (P < .001). Diffuse myocardial fibrosis could be detected by native T1 mapping in ESRD patients with long-term anemia. Anemia is an important factor in myocardial fibrosis in ESRD patients, and the evaluation of myocardial involvement is worth considering for clinical management.